PENINGKATAN MINAT BACA REMAJA MELALUI PERPUSTAKAAN DESA KERANO KUNCORO UNTUK MENGATASI KECENDERUNGAN REMAJA BERMAIN GAME ONLINE - Purwaka; Sa'diyah, Lailatus (BACA: Jurnal Dokumentasi dan Informasi, 2022)
The existence of useful and accounted sources of information generally are available in the library. Teenagers should be suggested to visit the library regularly. Efforts to lead teenagers to use the village library must be taken seriously by librarians. This research aims to explain how to increase the interest in reading through the village library of Kerano Kuncoro to overcome the online game trend. This research uses a qualitative approach. The subjects of this study were village library officer Kerano Kuncoro and library users that also a student. The Data collection methods use interview and observant data. The data is analyzed qualitatively through the stages of data collection, data reduction, presentation of data, and withdrawal of conclusions. The results obtained are: 1) the condition of the Kerano Kuncoro library room is quite comfortable for the library users; 2) the library collection is quite complete and diverse; 3) library officials are very cooperative with library users; 4) there is free wi-fi services; 5) teenagers are motivated to visit the village library regularly. Increased interest in reading through the village library to overcome the online game trend is vital. Before the Covid-19 pandemic, the average number of visitors per day was between 25 and 30. An average daily visit of at least 2 hours will automatically reduce their time to play online game. Researchers suggest the need for cooperation between the village library and the village government to organize a unique and exciting program; the village library should continue to try to complement and provide up-to-date collections.